1988
DOI: 10.1159/000234482
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Allergen-Specific T Cells by Conjugates of N-Formyl-Methionyl-Leucyl-Phenylalanine and Rye Grass Pollen Extract

Abstract: A conjugate of the biologically active peptide N-formyl-methionyl-leucyl-phenylalanine and rye grass pollen extract (F-MLP/rye), previously shown to react with rye grass pollen extract-specific T cells, induced the formation of allergen-specific T cells in mice. Lymph node cells prepared from mice immunized with either native extract or F-MLP/rye gave an enhanced response to unmodified rye grass pollen allergens in vitro. Syngeneic spleen macrophages were able to present the unmodified allergens to T cells obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1988
1988
2001
2001

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
(14 reference statements)
0
1
0
Order By: Relevance
“…For example, conju gates of polysarcosine and extract were shown to suppress the induction of murine IgE antibody re sponses via T-suppressor cell mechanisms [19]. Re cently we have shown that accessory cell-processed al lergen fragments produced by chymotryptic fission can stimulate T cells, and can also induce helper cells which collaborate with hapten-specific B cells in an adoptive transfer system [17], Conjugates between formyl-methionyl-leucyl-phenylalanine and extract were similarly presented by accessory cells and could induce delayed hypersensitivity in guinea pigs [3,20], In contrast to these results, the extract fragments, pro duced by fission with chemical reagents described here neither induced T cells which were able to collab orate in an adoptive transfer system nor gave delayed hypersensitivity reactions in guinea pigs; yet they were active in both murine and human lymphocyte proliferation assays.…”
Section: Discussionmentioning
confidence: 99%
“…For example, conju gates of polysarcosine and extract were shown to suppress the induction of murine IgE antibody re sponses via T-suppressor cell mechanisms [19]. Re cently we have shown that accessory cell-processed al lergen fragments produced by chymotryptic fission can stimulate T cells, and can also induce helper cells which collaborate with hapten-specific B cells in an adoptive transfer system [17], Conjugates between formyl-methionyl-leucyl-phenylalanine and extract were similarly presented by accessory cells and could induce delayed hypersensitivity in guinea pigs [3,20], In contrast to these results, the extract fragments, pro duced by fission with chemical reagents described here neither induced T cells which were able to collab orate in an adoptive transfer system nor gave delayed hypersensitivity reactions in guinea pigs; yet they were active in both murine and human lymphocyte proliferation assays.…”
Section: Discussionmentioning
confidence: 99%